Small aircraft transportation system in Poland – idea and model assumptions - Marciszewska, Elžbieta; Bergel, Izabella (Univerzita Pardubice, 2010)
The paper presents the idea of small aircraft transportation system in Poland based on research being done within a grant of Institute of Aviation along with Warsaw School of Economics and Warsaw Institute of Technology. The final aim of this system is to provide a fast means of transport to all Polish regions, especially the provision of business trips to/from any region in Poland within one day at the cost comparable to travelling by car. Within the research on SATS there was a series of investigation on intra-regional mobility, passenger flows estimation based on income distribution, time value and intraregional mobility statistical database. Direct research (questionnaire) involved three regions, 900 respondents (households and companies). Data gathered on intra-regional mobility is a basis for modelling the demand for SATS services, including formulation of transportation task, selection of aircraft and system workings. In the final phase of research an attempt will be made at working out a comprehensive idea of SATS workings in Poland along with flight and fleet management system, flight scheduling and service marketing. It is also assumed that SATS Data Collecting and Management System (System Wide Information Management) will be established within SESAR programme by 2020. During the research on SATS in Poland research and studies carried out within EPATS (European Personal Air Transportation System) project were used. These were a part of the Sixth Framework Programme of the EU.
Keywords: small aircraft transportation system; intra-regional flows; model assumptions